Regioselective Thiocyanation of Aromatic and Heteroaromatic Compounds by Using Boron Sulfonic Acid as a New, Efficient, and Cheap Catalyst in Water - Sami Sajjadifar; Omid Louie (Journal of Chemistry)
Highly efficient regioselective thiocyanations of indoles and N,N-disubstituted anilines are achieved via a green and simple protocol using boron sulfonic acid (BSA) as a new catalyst and KSCN/H2O2 as a mild and environmentally friendly oxidant in aqueous media.